Lama Tinggal Wisatawan Nusantara di Bandung - Djulius, Horas; Syafutra, Ricky (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
The tourists length of stay of is an important indicator characterizing the benefit of tourism in particular city. Therefore it is important to comprehend what factors related to tourist length of stay. In addition to obtaining the characteristics of domestic tourists visiting Bandung, this study also aims to determine the effect of spending, number of visits to attractions, the distance of the city of origin, and perception of security, comfort, congestion, and weather in Bandung Raya, to the tourists length of stay. The study was conducted through a survey of 100 tourists who were visiting the tourist attraction as respondents, which was chosen by cluster random sampling method. Variables that positively and significantly affect the length of stay are expenditure, distance of the city of origin, and perception of security. In the long run, if the tourist segmenting and targeting are not adjusted then it is very difficult for Bandung City to acquire longer lenght-of stay tourists.